The Psychological Factors Impacts on the Students’ Speaking Skill - Muhamad Rifqi Bakhtiar; Suwandi Suwandi (Universitas Negeri Semarang, 2022)
English speaking skill can be difficult for students in any educational levels and environments to acquire. The challenge is also encountered by the students of the Islamic-based schools. This is caused by several factors, one of which is psychology. With the aforementioned problem, the researchers intended to find out how the psychological factors could affect students’ speaking ability. The investigation of this study focused on exploring the impact of anxiety, self-confidence, motivation and shyness on Islamic boarding school EFL learners’ speaking abilities. The research design is qualitative with observations, questionnaires, and interviews employed as the research instruments. Based on the analysis, state anxiety appeared to be the main problem for the students. Shy pupils avoid speaking, offer brief responses to queries in the target language, and prefer to remain alone. They have modest communication challenges, are sluggish to express their emotions, and often do not respond when others express their emotions. Self-confidence has an influence on pupils' speaking abilities. In other words, students with high self-confidence are more likely to speak English better than those of with low self-confidence. Another psychological factor - motivation could be influenced by two aspects: internal and external forces. The study's description is likely to be utilized as a consideration for other researchers conducting more research on psychological aspects influencing students' speaking ability in the English classroom.